Genus dicendi y verdad. A propósito de Ortega - Chamizo Domínguez, Pedro J. (Revista de Filosofía, 2009)
The aim of this paper is to explore the main characteristics of the essay as philosophical genus dicendi and how they are fulfilled in Ortega’s works. Consequently, I firstly analyze the main four characteristics of the essay, namely, search for truth, cognitive value of opinions, rejection of the argument from authority, and intellectual tolerance. And secondly, I demonstrate how they have been taken into account by Ortega in his philosophical writings.
Keywords: Ortega; Essay; Truth; Genus dicendi; Opinion; Tolerance